2015
DOI: 10.1371/journal.pone.0119382
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Signaling and Proteolytic Enzyme Activity in Cardiac and Skeletal Muscle of Spontaneously Hypertensive Rats following Chronic Aerobic Exercise

Abstract: Hypertension is a cardiovascular disease associated with deleterious effects in skeletal and cardiac muscle. Autophagy is a degradative process essential to muscle health. Acute exercise can alter autophagic signaling. Therefore, we aimed to characterize the effects of chronic endurance exercise on autophagy in skeletal and cardiac muscle of normotensive and hypertensive rats. Male Wistar Kyoto (WKY) and spontaneously hypertensive rats (SHR) were assigned to a sedentary condition or 6 weeks of treadmill runnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 66 publications
7
25
0
1
Order By: Relevance
“…The same study found no changes to Atrogin-1 expression [100]. Protein amounts of MuRF1 and Atrogin-1 (that were not quantified in the present study) were recently shown to remain stable after 6 weeks of treadmill activity (5 days/week) when measured in the gastrocnemius muscles of male Wistar Kyoto rats at 11 weeks of age [101]. Thus, it appears that key markers of proteasomal degradation are relatively unaffected in both human and rodent muscles in response to chronic forms of exercise training.…”
Section: Discussionmentioning
confidence: 54%
“…The same study found no changes to Atrogin-1 expression [100]. Protein amounts of MuRF1 and Atrogin-1 (that were not quantified in the present study) were recently shown to remain stable after 6 weeks of treadmill activity (5 days/week) when measured in the gastrocnemius muscles of male Wistar Kyoto rats at 11 weeks of age [101]. Thus, it appears that key markers of proteasomal degradation are relatively unaffected in both human and rodent muscles in response to chronic forms of exercise training.…”
Section: Discussionmentioning
confidence: 54%
“…Nonetheless, the tendency for a reduced LC3 II to LC3 I ratio between days 3 and 7 suggests that muscle autophagic flux may become more activated when the CCA-induced mitochondrial adaptations culminate. Likewise, other studies have also claimed that endurance exercise training decreased the LC3 II to LC3 I ratio in the skeletal muscle of humans (Fritzen et al 2016) and rodents (McMillan et al 2015), probably due to the increase in LC3 I protein abundance.…”
Section: Discussionmentioning
confidence: 82%
“…; McMillan et al. ; Tam et al. ) term endurance training do not alter those transcript and/or protein levels in skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…), but some opposing results have also been documented (McMillan et al . ; Mejías‐Peña et al . ; Kim & Hood, ).…”
Section: Discussionmentioning
confidence: 99%